Pemberitaan Politik Fajar.co.id: Sebuah Studi Kebijakan Redaksional terkait Pemilu Walikota Makassar - Marua, Ardan; Muzakkir, Abd. Kahar (SIGn Journal of Social Science, 2022)
This research explore Fajar.co.id’s editorial policies and editorial management process in political reporting, particularly concerning the 2020 Makassar Mayoral Election. This research uses an inductive qualitative analysis. Inductive analysis is an approach that begins with field facts, analyzes them based on relevant theories and arguments, and ultimately yields a conclusion. The results show that Fajar.co.id’s editorial policy in reporting the 2020 Makassar Mayoral Election prioritizes newsworthiness by ensuring each published news piece is widely discussed, offers interesting perspectives, and uses language easily understood by a broad spectrum of society from various backgrounds. The applied editorial management demonstrates that content control occurs in the initial writing phase, with editors playing a crucial role in editing and gatekeeping functions. Although published news becomes public domain, the editorial team remains responsible for ensuring the accuracy and integrity of content by correcting writing errors without altering the news substance. Therefore, it is recommended that Fajar.co.id’s editors and reporters continue honing their abilities in identifying and processing issues with high news value and social relevance while maintaining a balance between commercially appealing news and the importance of information for public interest. Fajar.co.id must keep its motto ‘wisdom on the unbiased line’. Furthermore, the importance of ongoing training in language skills enhancement to communicate news effectively to a diverse reader while ensuring that every presented news piece adheres to ethical journalism principles is emphasized. Additionally, the already robust control and gatekeeping system should continue to be strengthened to ensure any factual or linguistic errors can be promptly corrected without altering the essence of the news, to uphold and enhance Fajar.co.id’s credibility as a responsible and reliable news media.